FADD and caspase-8 mediate priming and activation of the canonical and non-canonical Nlrp3 inflammasomes - Gurung, Prajwal (2014)
The Nlrp3 inflammasome is critical for host immunity, but the mechanisms controlling its activation are enigmatic. Here, we show that loss of FADD or caspase-8 in a RIP3-deficient background - but not RIP3-deficiency alone - hampered transcriptional priming and post-translational activation of the canonical and non-canonical Nlrp3 inflammasome. Deletion of caspase-8 in the presence or absence of RIP3 inhibited caspase-1 and caspase-11 activation by Nlrp3 stimuli, but not the Nlrc4 inflammasome. FADD deletion in addition prevented caspase-8 maturation, positioning FADD upstream of caspase-8. Consequently, FADD- and caspase-8-deficient mice had impaired IL-1β production when challenged with LPS or infected with the enteropathogen C. rodentium. Thus, our results reveal FADD and caspase-8 as apical mediators of canonical and non-canonical Nlrp3 inflammasome priming and activation.